2014
DOI: 10.1371/journal.pone.0110499
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Individual Double Burden of Overweight and Micronutrient Deficiencies among Vietnamese Women

Abstract: BackgroundVietnamese Living Standard Surveys showed that the rate of overweight and obese in Vietnamese adults doubled between 1992 and 2002, from 2% to 5.5%, respectively with no significant difference in the proportions of overweight/obesity between men and women.ObjectivesConsidering the increasing public health concern over the double burden of malnutrition in Vietnam, we investigated micronutrient deficiencies among women of reproductive age according to their Body Mass Index.MethodsA transversal study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 28 publications
4
37
2
1
Order By: Relevance
“…Low plasma retinol concentrations and a higher prevalence of marginal VitA status among underweight women were reported from the mentioned study in Vietnam [35]. The authors showed that food energy intake among participants increased along the BMI classifications and concluded that higher micronutrient intakes could have resulted in a better VitA status of individuals with a BMI > 18.5 kg/m 2 .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Low plasma retinol concentrations and a higher prevalence of marginal VitA status among underweight women were reported from the mentioned study in Vietnam [35]. The authors showed that food energy intake among participants increased along the BMI classifications and concluded that higher micronutrient intakes could have resulted in a better VitA status of individuals with a BMI > 18.5 kg/m 2 .…”
Section: Discussionmentioning
confidence: 90%
“…But, the inverse relationship between BMI and iron status has been consistently reported by others, especially in overweight/obese compared to normal weight individuals [34]. On the contrary, a cross-sectional study among 1530 Vietnamese women of reproductive age reported positive associations between BMI with Hb and plasma FER, although this was not associated with a different prevalence of anemia or iron deficiency among different BMI groups [35]. …”
Section: Discussionmentioning
confidence: 92%
“…After applying the inclusion and exclusion criteria, a total of 26 original studies were ultimately included in the meta‐analysis (Fig. ), including 21 cross‐sectional studies and 5 case–control studies ; no cohort studies were include in the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…11 Laillou et al (2014) [28] Intraindividual DBMN among Vietnamese women Intraindividual DBMN (overweight/obesity and micronutrient deficiency) was observed among women.…”
Section: Dbmn At the Community Levelmentioning
confidence: 99%